Effect of CaCO3 on the Gaseous Reduction of Tin Oxide Under CO-CO2 Atmosphere. (3rd May 2016) - Su, Zijian; Zhang, Yuanbo; Liu, Bingbing; Chen, Jun; Li, Guanghui; Jiang, Tao
ABSTRACT: Calcite (CaCO3 ), one of the main impurities, has an uncertain effect on the volatilization behavior of tin oxide in the tin-bearing iron ore concentrates during the selective reduction volatilization process. In this study, natural calcite powders were added into the tin-bearing iron ore concentrates to investigate tin volatilization behavior affected by CaCO3 under different roasting temperature, CO content, and roasting time. In addition, the effect of CaCO3 on the phase transformation of SnO2 was determined using XRD, SEM-EDS combined with thermodynamics calculation. The results indicated that CaCO3 had a significantly adverse effect on the Sn volatilization ratio, because Ca2 SnO4 was easily formed under CO-CO2 atmosphere. It was also found from the study that the generation of SnO(s) was the most critical intermediate for promoting the formation of Ca2 SnO4 .